Sistem Informasi Koperasi Simpan Pinjam Mitra Duta Artha Pule Berbasis Website - Anjung Adi Kiswara; Aris Setiawan Indras Pratama; Tjatursari Widiartin (Melek IT : Information Technology Journal, 2022)
Extreme Programming (XP) is a software engineering process that tends to use an object-oriented approach and the target of this method is a team formed on a small to medium scale and this method is also suitable if the team is faced with unclear requirements or changing requirements. which is very fast. The research activity carried out at the Mitra Duta Artha Pule Cooperative is to create a savings and loan information system to facilitate staff in conducting and processing transaction data. With the implementation of the Mitra Duta Artha Pule Cooperative Information System, it is hoped that the management will be able to disseminate information to related management and also to cooperative members, so that the use of the system can be utilized properly and optimally.